2020
DOI: 10.1002/ece3.6604
|View full text |Cite
|
Sign up to set email alerts
|

Higher host plant specialization of root‐associated endophytes than mycorrhizal fungi along an arctic elevational gradient

Abstract: How community‐level specialization differs among groups of organisms, and changes along environmental gradients, is fundamental to understanding the mechanisms influencing ecological communities. In this paper, we investigate the specialization of root‐associated fungi for plant species, asking whether the level of specialization varies with elevation. For this, we applied DNA barcoding based on the ITS region to root samples of five plant species equivalently sampled along an elevational gradient at a high ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 101 publications
1
18
1
Order By: Relevance
“…We further found that warming influenced the fungal community composition, with a particularly strong effect towards the end of the growing season. In line with this finding, several observational studies have reported shifts in the composition of foliar fungal communities along altitudinal and elevational gradients, which are often used as proxies for changes in climate (Hashizume et al ., 2010; Cordier et al ., 2012; Davey et al ., 2013; Coince et al ., 2014; Whitaker et al ., 2018; Abrego et al ., 2020a,b; Cai et al ., 2020). However, findings along such gradients are often confounded by concurrent changes in abiotic and biotic environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We further found that warming influenced the fungal community composition, with a particularly strong effect towards the end of the growing season. In line with this finding, several observational studies have reported shifts in the composition of foliar fungal communities along altitudinal and elevational gradients, which are often used as proxies for changes in climate (Hashizume et al ., 2010; Cordier et al ., 2012; Davey et al ., 2013; Coince et al ., 2014; Whitaker et al ., 2018; Abrego et al ., 2020a,b; Cai et al ., 2020). However, findings along such gradients are often confounded by concurrent changes in abiotic and biotic environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Thus, the presence of endophytic fungi can provide host plants with several benefits, such as resistance to attack by herbivores, heat and drought, in addition to promoting growth and increasing nutrient recycling. [18 -20] According to Azevedo, [20] endophytic microorganisms can be found in the tissues of all plants studied around the world, including those in tropical forests, [7] coastal forests, [21] deserts, [22] Brazilian savannas, [23] tundra, [24] mangroves, [25] Antarctica, [26] the Arctic region, [27] Pantanal, [28] and prairies. [29] Some works have reported that secondary metabolites of fungi are also produced by the respective host plant, which may be related to a horizontal transfer of genes that may have occurred during the co-evolution between the endophytic fungus and the host plant.…”
Section: Endophytic Fungimentioning
confidence: 99%
“… 2019 ; Abrego et al . 2020 ; Arraiano-Castilho et al . 2020 ; Fujimura and Egger 2012 ; Garnica et al .…”
Section: Plant-associated Microbial Communities In Alpine Regionsmentioning
confidence: 99%
“… 2019 ; Abrego et al . 2020 ). However, plant species have variable effect on the plant-associated fungal communities depending on the fungal group (e.g.…”
Section: Plant-associated Microbial Communities In Arctic Regionsmentioning
confidence: 99%
See 1 more Smart Citation